KAJIAN KARAKTERISTIK DAN DEFORMASI CAMPURAN AC-WC DENGAN PENGGUNAAN SUBTITUSI LIMBAH MARMER SEBAGAI FRAKSI AGREGAT KASAR - Bea, Liliyan; Basri, Lambang; Alifuddin, Andi (Ikatan Dosen Menulis, 2023)
Repetitive and excessive load pressure by vehicles is one of the damages that occurs on road pavement deformation due to the pavement layer losing its strength, causing the road layer to subside and cracks to occur. Marble waste is the remaining waste acquired from the processing of the marbles. Environmental pollution is caused by the marble processing process. The marble waste produced is increasing gradually over time, therefore, it is needed to utilize that marble waste. The marble waste is expected to improve the quality and performance of the mixture in resisting deformation in the AC-WC mixture and has good mixture characteristics. This research aims to examine the cause of using marble waste on the characteristics and deformation of the mixture. The test in this research applies the marshall test and wheel tracking tool. The result showed that the characteristics of the mixture and KLMO, total deformation, deformation rate, and dynamic stability using KAO 6% and the Optimum Marble Waste Content (KLMO) obtained was 25%. The highest stability and Marshall Quatient were 1024.89 kg and 345.65 kg/mm at 25% marble waste variation. The lowest flow value in the mixture with 25% marble waste variation was 2.97 mm. The 25% variation has good mixture characteristics and durability. The smallest total deformation was 0.903 mm at 25% marble waste variation, dynamic stability 2864 passes/mm, and deformation rate 0.0147 mm/minute.